2012
DOI: 10.1007/s00125-012-2533-1
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD163: a biomarker linking macrophages and insulin resistance

Abstract: Aims/hypothesis Soluble CD163 (sCD163) was recently identified as a strong risk marker for developing type 2 diabetes. We hypothesised that sCD163 independently associates with insulin resistance. Methods This cross-sectional study includes 234 participants: 96 with type 2 diabetes, 34 with impaired glucose tolerance (IGT) and 104 with normal glucose tolerance (NGT), matched for sex and BMI. Glucose-lowering medication was paused for 1 week before plasma samples were obtained for determination of sCD163 and ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
73
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 30 publications
14
73
3
Order By: Relevance
“…We did not find any association to glucose variables, presumably because increased fasting and post-load glucose are relatively late events in the pathogenesis of dysglycaemic progression, and because participants with diabetes diagnosed during follow-up were excluded by our study design. Our finding of time-independent associations between sCD163 and insulin resistance and insulin secretion strengthens the evidence from previous cross-sectional studies [7,20]. Our study is in agreement with other studies that found adiponectin to be negatively associated with changes in post-load glucose, insulin resistance and insulin secretion [21][22][23].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We did not find any association to glucose variables, presumably because increased fasting and post-load glucose are relatively late events in the pathogenesis of dysglycaemic progression, and because participants with diabetes diagnosed during follow-up were excluded by our study design. Our finding of time-independent associations between sCD163 and insulin resistance and insulin secretion strengthens the evidence from previous cross-sectional studies [7,20]. Our study is in agreement with other studies that found adiponectin to be negatively associated with changes in post-load glucose, insulin resistance and insulin secretion [21][22][23].…”
Section: Discussionsupporting
confidence: 93%
“…High circulating levels of sCD163 are associated with obesity, insulin resistance and type 2 diabetes mellitus in cross-sectional studies [7][8][9]. sCD163 is furthermore associated with incident type 2 diabetes mellitus in a prospective study [10].…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, there is a significant association between the insulin resistance measured by HOMA-IR and the level of sCD163 and the expression of CD163 in obese subjects (Zanni et al 2011, Fjeldborg et al 2013, Kračmerováet al 2014. Finally, sCD163 is found to be strongly associated with the development of type 2 diabetes (Parkner et al 2012).…”
Section: Introductionmentioning
confidence: 94%
“…pioglitazone) to improve insulin sensitivity and decrease risk of CVD events [58,59]. Due to the fact that many of these drugs have been shown to affect adipose tissue differentiation, inflammation, and consequently insulin sensitivity [60][61][62], studies have began to focus on adipose tissue as another important organ contributing to CVD risk in obese populations [63,64].…”
Section: Mechanisms Of Insulin Resistance Hyperglycemia and Dyslipimentioning
confidence: 99%